COVID-19 and Black Lives Matter: Examining Anti-Asian Racism and Anti-Blackness in US Education (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The spread of COVID-19 and the uprisings following the murder of George Floyd has brought the United States to a moment of racial reckoning. The hitherto ignored and hidden impacts of race and racism has captured public imagination at the intersection of this pandemic and the Black Lives Matter movement in the US. Institutions of higher education have a critical role and responsibility to spearhead transformative justice and change.